Cycling capitals. - (:unkn) unknown (Deutsches Institut für Urbanistik (Difu), 2013)
The international cycling capitals use a wide range of political strategies and planning approaches. Bicycle planning is conceived as part of integrated transport and urban planning schemes. This notion is often premised on the general principle of a 'short journey city' and the strengthening of active travel in a compact settlement structure. In this environment, the bicycle can be established as the dominant means of transport. At the same time this requires consistent measures to reduce car use. A citywide cycling strategy can serve to bring together different stakeholders and activities within a formal common framework.
Keywords: Fahrradinfrastruktur; Radverkehrsplanung; Radverkehrsförderung; Fahrradförderung; Mobilitätsverhalten; Radverkehrsplanung; Fahrradfreundliche Stadt; Münster; Oldenburg; Kiel; Individualverkehr; Fahrradverkehr